The effect of guided breastfeeding education on skill and attitude towards breastfeeding practice among first-time mothers in Jordan - Al-Radaydah, Dana Saleh Mohammad (2021)
Breastfeeding is a well-known feeding method for infants. Education on breastfeeding is important in promoting the breastfeeding practice especially among first time mothers. The goal of educating mothers is not only to increase their breastfeeding knowledge and skills but also to influence their breastfeeding practice. This study aimed to determine the effectiveness of postnatal guided breastfeeding education program on breastfeeding skills and attitude among first-time mothers and to determine their breastfeeding practice. This is a quasi-experimental design study to investigate the effect of guided postnatal breastfeeding educational intervention on breastfeeding skills and attitude. A sample of 87 first time mothers (intervention = 44, control = 43) from Princess Badea'a Hospital (PBH) in Irbid, Jordan had completed the study. Data was collected using the Iowa Infant Feeding Attitude Scale (IIFAS) and LATCH Assessment Tool at pre-intervention phase (within 4 hours postpartum) and post intervention (at 8 weeks postpartum). Paired t-test analysis was used to determine the mean score different within groups and independent t-test analysis was used to compare mean score different between both groups. Results showed that there was significant increase in breastfeeding skills and attitude among the intervention group as compared to the control group. A 43.2% of first-time mothers in the intervention group and 20.9% in the control group continued exclusive breastfeeding at 6 months post-delivery. Postnatal guided breastfeeding education program is beneficial to improve the breastfeeding skill and the attitude towards breastfeeding especially among first time mothers.